2013
DOI: 10.1186/2211-1522-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Two simple, brief, naturalistic activities and their impact on positive affect: feeling grateful and eating ice cream

Abstract: Background: Positive psychology interventions have been shown to increase happiness and well-being, and researchers are beginning to speculate on the mechanisms through which these interventions may be effective. People are also naturally attuned to the things that will make them happier in their daily lives, and there is a case for considering how more naturalistic, everyday activities may also increase positive affect, happiness and well-being. Methods: Study 1 involved 89 participants who completed a gratef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
(41 reference statements)
2
4
0
1
Order By: Relevance
“…Second, eating an ice cream was found to increase positive emotional intensity and Positive Affect. These findings lend support for hypothesis 2 that eating ice cream alone is effective in increasing general Positive Affect and discrete positive emotions and are in line with previous research findings (e.g., Isen & Levin, 1972;Linley et al, 2013). It is notable that there was a difference in Positive Affect scores of 3.5 points (equivalent to a Positive Affect score greater by 11.9%) between people who consumed an ice cream and people who neither consumed an ice cream nor gifted an ice cream to someone else.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Second, eating an ice cream was found to increase positive emotional intensity and Positive Affect. These findings lend support for hypothesis 2 that eating ice cream alone is effective in increasing general Positive Affect and discrete positive emotions and are in line with previous research findings (e.g., Isen & Levin, 1972;Linley et al, 2013). It is notable that there was a difference in Positive Affect scores of 3.5 points (equivalent to a Positive Affect score greater by 11.9%) between people who consumed an ice cream and people who neither consumed an ice cream nor gifted an ice cream to someone else.…”
Section: Discussionsupporting
confidence: 81%
“…Ice cream is frequently used by popular media as an example of a mood food, but only a few studies have investigated scientifically the effects of ice cream on mood. For example, Linley et al (2013) demonstrated that eating ice cream while thinking of things for which one was grateful led to increases in Positive Affect (Study 1), and subsequently that thinking of things for which one was grateful and eating ice cream, whether doing both together or separately, led to increases in Positive Affect (Study 2). Walla, Richter, Farber, Leodolter and Bauer (2010) compared the effects of eating ice cream with those of eating yoghurt and of eating chocolate.…”
Section: Eating Desirable Foods As a Naturalistic Source Of Positive mentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the few studies to take a naturalistic approach to enhancing happiness, Parks, Della Porta, Pierce, Zilca and Lyubomirsky (2012) found that, on average, people performed their chosen happiness increasing strategies several times a week for at least an hour each time. Linley, Dovey, de Bruin, Transler, Wilkinson, Maltby and Hurling (2013) also found everyday activities already performed in people's life, such as pleasurable eating, can also, at least temporarily, increase levels of positive affect. Perhaps we can further boost the impact of our interventions by matching them to a person's context and reducing barriers to their implementation by making them extremely easy for people to enact?…”
Section: Introductionmentioning
confidence: 78%
“…A fin de hacer frente al estrés cotidiano actualmente existe un amplio repertorio de actividades recomendadas para manejarle como el hacer deporte o caminar, escuchar música, leer, ver la televisión, utilizar videojuegos, es decir, utilizar algún tipo de pasatiempo. La razón que se da para su uso es que estos permiten tanto una mejora general de la salud como efectos sobre las emociones (APA, 2010;Linley et al, 2012). Como un medio capaz de fomentar la expresión y con ello, el manejo de conflictos, de los anteriores pasatiempos las actividades como el dibujo o la pintura son utilizadas también en ambientes clínicos con fines terapéuticos (American Art Therapy Association, AATA, 2013).…”
unclassified